Loss of the Nf1 Tumor Suppressor Gene Decreases Fas Antigen Expression in Myeloid Cells - Hiatt, Kelly (American Society for Investigative Pathology, 2004)
Genetic loss of surface Fas antigen expression leads to reduced apoptosis of myeloid and lymphoid progenitor cells, and a propensity to develop autoimmunity and myeloid leukemia in mouse models. Oncogenic p21(ras) decreases surface Fas antigen expression and renders fibroblasts resistant to Fas mediated apoptosis. Neurofibromin, which is encoded by NF1, is a GTPase activating protein that negatively regulates p21(ras) activity. NF1 loss leads to deregulation of p21(ras)-effector pathways, which control myeloid cell survival. Heterozygous inactivation of Nf1 increases mast cell numbers in Nf1 +/− mice, and enhances mast cell survival in response to c-kit ligand (kit-L). Here, we show that Nf1-deficient mast cells have reduced surface Fas antigen expression in response to kit-L and are resistant to Fas ligand-mediated apoptosis. Using genetic intercrosses between Nf1 +/− and class I (A)-PI-3K-deficient mice, we demonstrate that hyperactivation of the p21(ras)-class I(A) PI-3K pathway is the mechanism for this phenotype. Finally, we demonstrate that mast cells from both Fas antigen-deficient mice and Nf1 +/− mice are resistant to apoptosis following kit-L withdrawal in vivo. Thus, therapies designed to decrease p21(ras) activity and up-regulate Fas antigen expression may limit the pathological accumulation of myeloid cells in disease states where p21(ras) is hyperactivated.